Impact of the Spring North Atlantic Oscillation on the Northern Hemisphere Tropical Cyclone Genesis Frequency - Zhang, Leying; Yang, Xiting; Zhao, Jiuwei (Frontiers in Earth Science, 2022)
Majority studies have documented basin-dependent factors for predicting interannual variability of tropical cyclone genesis frequency (TCGF) over basins. In this study, we find that the spring North Atlantic Oscillation (NAO) has cross-basin impacts on summer and autumn TCGF over the whole North Hemisphere. The positive NAO suppresses the TCGF in the North Atlantic (NA) but promotes the TCGF in the North Pacific (NP) via modulating the large-scale environment parameters, and vice versa. The positive NAO in spring can induce negative sea surface temperature (SST) anomalies in the NA, which persists into summer via the ocean memory. The negative SST anomalies cool the overlying atmosphere and damp the precipitation, leading to a low-level anti-cyclonic circulation and thereby counteracting the TCGF over the NA in summer and autumn. The southerly anomaly west of the anti-cyclonic circulation increases the SST and precipitation over the northeast Pacific in summer. Accordingly, a cyclonic circulation appears western NP via Gill response and sustains by the warm advection via the air-ocean positive feedback, which devotes the NP TCGF in summer and autumn. The composite results in high-resolutions numerical model from Coupled Model Inter comparison Project Phase 6 further verify the relationship between the spring NAO and TCGF.